The effect of 8-weeks of combined resistance training and chocolate milk consumption on maximal strength, muscle thickness, peak power and lean mass, untrained, university-aged males - Yapici, Hakan; Gülü, Mehmet; Yagin, Fatma Hilal; Ugurlu, Dondu; Comertpay, Ertan; Eroglu, Oguz; Kocoğlu, Melike; Aldhahi, Monira I.; Karayigit, Raci; Badri AL-Mhanna, Sameer (Frontiers in Physiology, 2023)
The overarching aim of this study was to investigate the combined effects of chocolate milk consumption (500 mL) with 8-week of resistance training on muscle hypertrophy, body composition, and maximal strength in untrained healthy men. A total of 22 Participants were randomly divided into two experimental groups: combined resistance training (3 sessions per week for 8 weeks) and chocolate milk consumptions (include 30 g protein) Resistance Training Chocolate Milk (RTCM) (Age: 20.9 ± 0.9 years old) and resistance training (RT) only (Age: 19.8 ± 0.7 years old). Muscle thickness (MT), using a portable ultrasound, body composition, body mass, maximal strength (one repetition maximum (1 RM), counter movement jump (CMJ) and peak power (PP) were determined at baseline and 8 weeks later. In the RTCM, finding showed a significant improvement in the outcomes compared to the RT group, besides the main effect of time (pre and post). The 1 RM total increased by 36.7% in RTCM group compared to 17.6% increased in the RT group (p < 0.001). Muscle thickness increased by 20.8% in the RTCM group and 9.1% in the RT group (p < 0.001). In the RTCM group, the PP increased by 37.8% compared to only 13.8% increase in the RT group (p = 0.001). The group*time interaction effect was significant for MT, 1RM, CMJ, and PP (p < 0.05), and it was observed that the RTCM and the 8-week resistance training protocol maximized performance. Body fat percentage (%) decreased more in the RTCM (18.9%) group than in the RT (6.7%) group (p = 0.002). In conclusion, chocolate milk (500 mL) with high protein content consumed in addition to resistance training provided superior gains in terms of MT, 1 RM, body composition, CMJ, and PP. The finding of the study demonstrated the positive effect of casein-based protein (chocolate milk) and resistance training on the muscle performance. Chocolate milk consumption has a more positive effect on muscle strength when combined with RT and should be considered as a suitable post-exercise nutritional supplement. Future research could be conducted with a larger number of participants of different ages and longer study durations.